Use of Article 106(2) TFEU in the context of liberalizing the Latvian market of roadworthiness testing services - Žīgurs, Rolands (Riga Graduate School of Law, 2019)
The master’s thesis is about the potential use of the “escape clause” enshrined in Article 106(2) of the Treaty of the Functioning of the European Union (TFEU) in a situation where an undertaking, which is granted with special or exclusive rights and entrusted with the operation of services of general economic interest, might be liable for violating Article 102 TFEU in conjunction with Article 106(1) TFEU.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law